To Compare the Supraclavicular and Infraclavicular Approaches of Brachial Plexus Block for Upper Limb Surgery Using 0.05mg of Dexmedetomidine and 30ml of 0.5% Ropivacaine - Kaur, Dr. Balwinder; Grewal, Dr Tejinderpal Kaur; Aggarwal, Dr. Shelly (International Journal of Innovative Research in Medical Science, 2019)
Purpose: This prospective study is to compare the supraclavicular and infraclavicular approaches of brachial plexus block for upper limb surgery using 0.05mg of dexmedetomidine and 30ml of 0.5% ropivacaine. Method: This prospective, randomized controlled trial was conducted at Govt. Medical College, Rajindra Hospital, Patiala on sixty patients in two groups (group S and group I) of 30 each of 18 to 65 yrs of age of either sex of ASA grade I or II scheduled for upper limb surgery. In both supraclavicular and infraclavicular approach the drug injected was 30ml of 0.5% ropivacaine and 0.05mg of dexmedetomidine. Result: We found that in patients with comparable demographic parameters there was no statistically significant difference in hemodynamic parameters, onset and duration of sensory and motor block, duration of analgesia and patient satisfaction score between the groups. There was no statistically significant difference in the quality of block in either group. No episode of pneumothorax, Horner’s syndrome or local anaesthesia toxicity occurred in any of the group. Accidental vascular puncture occurred in four out of thirty patients in supraclavicular group and none in infraclavicular group. Conclusion: This study concluded that infraclavicular approach is more safe than supraclavicular approach in upper limb surgeries (elbow proximally to hand distally).